Vitellogenesis of diphyllobothriidean cestodes (Platyhelminthes) - Yoneva, Aneta; Scholz, Tomáš; Bruňanská, Magdaléna; Kuchta, Roman (Comptes rendus biologies, 2015)
The recently erected cestode order Diphyllobothriidea is unique among all tapeworm orders in that its species infect all major groups of tetrapods, including man. In the present paper, the vitellogenesis of representatives of all three currently recognized families of this order was evaluated, based on ultrastructural (transmission electron microscopy) and cytochemical (detection of glycogen) observations. Vitelline follicles of all taxa studied, i.e. Cephalochlamys namaquensis from clawed frogs (Xenopus), Duthiersia expansa from monitors (Varanus) and Schistocephalus solidus that matures in fish-eating birds, contain vitelline cells at various stages of development and interstitial cells. Developing vitellocytes are characterized by the presence of mitochondria, granular endoplasmic reticulum and Golgi complexes involved in the synthesis of shell globules and formation of shell globule clusters. Mature vitellocytes contain lipids and glycogen in different proportions. The most significant differences among the three diphyllobothriidean families were found in the presence or absence of lamellar bodies. Variations of vitelline clusters morphology and types of lipid droplets are described and discussed in relation to the presumed evolutionary history of diphyllobothriideans, which belong to the most basal cestode groups.
Keywords: vitelogeneze; Cestode Infections; Glycogen; Schistocephalus solidus; lipidy; zvířata; Ultrastructure; Duthiersia expansa; Vitellins; cestodózy; viteliny; Lipids; transmisní elektronová mikroskopie; Microscopy, Electron, Transmission; Animals; Diphyllobothriidea; glykogen; Vitellogenesis; Cephalochlamys namaquensis; Cestoda